Anaphylaxis and mortality induced by treatment of mice with anti-VLA-4 antibody and pertussis toxin - Ji, Niannian (2011)
Antibody-mediated blockade of the adhesion molecule very late antigen-4 (VLA-4) has been shown to ameliorate disease in human multiple sclerosis (MS) patients and experimental autoimmune encephalomyelitis (EAE) animal models. We wanted to determine whether anti-VLA-4 antibody treatment affected the function and persistence of autoreactive T cells in mice with EAE. Unexpectedly, we observed a high level of mortality in anti-VLA-4 mAb (PS/2) treated mice with actively induced EAE despite decreased disease severity. Investigation of the underlying mechanism showed that injection of PS/2 mAb in combination with pertussis toxin (PTX) resulted in anaphylaxis and mortality. Furthermore, the data showed that CD4(+) T cells were required for this effect and suggested a role for IL-1β and TNF-α in the underlying pathology. The results reveal a previously not appreciated deleterious effect of anti-VLA-4 antibody treatment in combination with exposure to PTX.